Economic Impact of Climate Change on Smallholder Crop Farms in Nigeria (2015)
The negative effect of Climate Change (CC) on agriculture across Africa has been well established. This underscores its global policy interest. In Nigeria, crop farming is climate dependent and farmholders often employ measures that are sub-optimal against climate risk. This raises the vulnerability of farming to CC uncertainty. For a long time, knowledge of CC perception by farmholders dominated the existing literature. However, information on economic estimates of damages and responses at the farm level is relatively scanty. Economic impact of CC on smallholder crop farms was therefore investigated. General household survey data on smallholder farms collected by the National Bureau of Statistics (NBS) in 2010 was used together with baseline climate observations from 1950-2000 and projections (2000-2050) of the World Climate Data Base (WCDB). Complementary data on population, soil and altitude for 774 Local Government Areas (LGA) were sourced from National Population Commission (NPC) and Food and Agriculture Organisation (FAO). Variables from NBS were farm value, farm revenue, crops cultivated, land size, area planted, household size and age. Variables from WCDB were Mean Temperature (MT) and Mean Precipitation (MP) for wet and dry seasons. Data was analysed using descriptive statistics, multivariate probit and Ricardian models at ∝0.05 Farm value and annual farm revenue were 156293.3 (10714.3-1619433.0) N/ha and 47837.1 (3966.2-2159244.3) N/ha respectively. Land size was 2.7±1.9 ha while area planted, household size and age were 2.3±18.2 ha, 5.2±1.6 and 51.3±15.3 years respectively. Baseline MT and MP were 26.3±2.9 ℃and 179.2±75.1 mm/month respectively for wet season and 25.9±3.0 ℃ and 22.3±24.7 mm/month for the dry season. Projected MT and MP were 27.61±3.0 ℃ and 192.3±61.6 mm/month for wet season and 27.5±3.0 ℃ and 25.6±29.3 mm/month for dry season respectively. Baseline MP increased the probability of cultivating sorghum (0.5%), cowpea (0.2%), and yam (0.1%) while it reduced the probability of cultivating millet (0.8%), rice (0.1%), cassava (0.1%) and maize (0.5%). Baseline MT increased the probability of cultivating millet (5.8%), rice (2.4%) and maize (51.5%) and reduced the probability of cultivating sorghum (0.7%), cowpea (2.1%), cassava (0.7%) and yam (36.7%). Projected MT reduced the probability of cultivating all crops with the highest probability on sorghum (10.5%). While the effect of projected MP on the probability of cultivation was mixed across crops, the highest probability of reduced cultivation was observed for rice (25.9%) and the least for maize (1.8%). Controlling for non-climate factors, climate change reduced farm value by 62.8% for the whole country and across agricultural zones by 8.2%, 41.9%, 7.2% and 41.0% for North central, North east, North west, and South west respectively except for South east that increased marginally by 3.4%. Climate change affected revenue and crop cultivation of smallholders and could affect food security in the near future. Impact was huge for the whole country and varies across agricultural zones. Use of stress tolerant technologies (irrigation, and drought tolerant seeds) and institutional support would enhance coping capacity against climate change risk